Risk Factors for Primary Hypertension - Juliansyah, Elvi; Masan, Lea; Haryanti, Yunida; Sunarti, Sunarti (Jurnal Kesehatan, 2024)
Hypertension is a deadly disease caused by high blood pressure, causing damage to the kidneys, heart, and brain. This study aims to determine the risk factors for hypertension related to family history, food, eating regularity, and physical activity with the incidence of primary hypertension in the community in Sintang District. This research method is a quantitative study with a cross-sectional method design, the population in this study was 699 people with a total sample of 97 respondents. The sampling technique used was a simple random sampling technique. The results of this study indicate that there is a significant relationship between family history and the incidence of hypertension, p-value of 0.001<(p-value=0.05) and OR of 4.800; there is a significant relationship between the type of food and the incidence of hypertension, p-value of 0.005<(p-value=0,05) and an OR of 4.680, there is a significant relationship between regular meals and the incidence of hypertension, p-value of 0.040< (p-value=0.05) and OR of 3.520, and there is a significant relationship between physical activity and the incidence of hypertension, p-value of 0.003< (p-value=0.05) and OR of 4.308. In conclusion, family history, type of food, regular food, and physical activity are related to the incidence of hypertension, therefore it is recommended that people who have a history of hypertension sufferers can regulate their diet and do physical activity regularly.